1991
DOI: 10.1159/000235388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Theophylline Compared with Prednisolone on Late Phase Airway Leukocyte Infiltration in Guinea Pigs

Abstract: The effects of prednisolone, theophylline or salbutamol treatment were studied on leukocyte numbers in bronchoalveolar lavage (BAL) fluid taken 72 h after ovalbumin challenge in sensitized guinea pigs. Ovalbumin challenge resulted in an approximate 3-fold increase in the number of eosinophils in BAL fluid. This increase was significantly reduced by oral administration of prednisolone (59% inhibition with 10mg/ kg × 2) theophylline (56% with 50 mg/kg × 2) but not by salbutamol (10 mg/kg × 2). A comparison with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 6 publications
3
13
2
Order By: Relevance
“…Our results contrast with those of others (Gristwood et al, 1991;Schudt et al, 1991;Underwood et al, 1993) who have demonstrated inhibitory effects on eosinophil accumulation by acute administration of PDE inhibitors. However, such differences may be attributable to differences in methodology between these studies and ours.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results contrast with those of others (Gristwood et al, 1991;Schudt et al, 1991;Underwood et al, 1993) who have demonstrated inhibitory effects on eosinophil accumulation by acute administration of PDE inhibitors. However, such differences may be attributable to differences in methodology between these studies and ours.…”
Section: Discussioncontrasting
confidence: 99%
“…Acute administration of theophylline and selective PDE isoenzyme inhibitors has been reported to reduce eosinophil infiltration induced by allergen challenge in sensitized guineapigs (Gristwood et al, 1991;Schudt et al, 1991;Manzini et al, 1993;Underwood et al, 1993 Pharmacology (1995) 114. 93-98 .…”
Section: Introductionmentioning
confidence: 99%
“…The inhibitory activity of PKA on rho activation in leukocytes may thus help explain the ability of some cAMP-elevating drugs to inhibit leukocyte transendothelial migration in vitro and recruitment and homing in vivo (17)(18)(19)(20)(21), phenomena that are dependent on chemoattractants and integrins. The effect may also permit cross-talk between pro-adhesive and anti-adhesive heterotrimeric G protein-linked receptors, potentially contributing, for example, to the inhibition of chemoattractant-induced neutrophil migration by adenosine, prostaglandin E1, or ␤ 2 -adrenergic receptors (22,23), G␣ s -linked serpentine receptors that activate adenylyl cyclase to produce cAMP.…”
mentioning
confidence: 99%
“…It is therefore possible that inhibition of antigen-induced AHR by rolipram may be due to modulation of C-fibre activity to reduce tachykinin release. Furthermore, this may explain the inhibitory effect of rolipram on ozone-induced AHR to inhaled histamine (Holbrook & Hughes, 1992) where the AHR is capsaicin sensitive and thought to be due to increased tachykinin effects resulting from oxidant damage of airway lumen neutral endopeptidase (Yeadon et al, 1992 (Griswood et al, 1991;Underwood et al, 1994;Lagente et al, 1994) and primate (Turner et al, 1994). Surprisingly, rolipram had no effect on neutrophil recruitment.…”
Section: Discussionmentioning
confidence: 99%